The class I protein AtTCP15 modulates plant development through a pathway that overlaps with the one affected by CIN-like TCP proteins - Uberti Manassero, Nora Graciela (2012)
The function of the class I TCP transcription factor TCP15 from Arabidopsis thaliana has been studied through the analysis of plants that express a fusion of this protein to the EAR repressor domain. Constitutive expression of TCP15-EAR produces growth arrest at the seedling stage, before leaf emergence. Expression of the repressor fusion from the AtTCP15 promoter produces small plants with leaves whose margins progressively curve upwards, starting from the basal part of the lamina. Leaves contain smaller and less differentiated cells, both on the adaxial and abaxial sides. The abaxial domain is relatively enlarged, with disorganized cells separated by empty spaces. TCP15-EAR also affects the growth of leaf petioles, flower pedicels, and anther filaments. Flowers show reduced elongation of the three outer whorls and altered gynoecia with irregular carpel surfaces and enlarged repla. Ectopic stigma-like structures develop from medial and basal parts of the replum. TCP15-EAR produces an increase in expression of the boundary-specific genes LOB, CUC1, and CUC2. Changes in CUC1 and CUC2 expression can be explained by the existence of lower levels of miR164 in leaves and the repression of IAA3/SHY2 and the SAUR-like gene At1g29460 in leaves and flowers. TCP15 binds to the promoter regions of IAA3/SHY2 and At1g29460, suggesting that these genes may be direct targets of the transcription factor. The results indicate that TCP15 regulates the expression of boundary-specific genes through a pathway that affects auxin homeostasis and partially overlaps with the one modulated by class II CIN-like TCP proteins.